The development of e-commerce as a factor stimulating economic growth - (:unkn) unknown (Scientific Herald of Uzhhorod University, 2024)
Global trends in the transition to the principles of the digital economy and the introduction of e-commerce as a factor of economic growth are increasingly becoming the object of research by scientists. The economy is becoming even more digital, and the past COVID-19 pandemic has contributed to this acceleration. The purpose of this study was to investigate the role of e-commerce and its essence in the economy digitalization, as a stimulating factor in the development of the country’s economy. The main methods of fulfilling the purpose of this study included the methods of systematic and structurallogical analysis of data, analysis and synthesis, generalization, prognostic method. The study strongly suggested that e-commerce has been developing at an accelerated pace all over the world in recent years. Both the announcement of the COVID-19 pandemic and the general trend towards the economy digitalization contributed to this. Global transformation processes continue and cover all spheres of life and production. The leaders are the countries of the world and, specifically, the countries of Europe. In Ukraine and Kazakhstan, programs for the economy digitalization of the countries have been developed, which are based on the principles “the state in a smartphone” and consider all elements of the structure of e-commerce. The most promising areas are the development of digital platforms, cloud services, electronic banking support, information protection, etc. The support of Industry 4.0 technologies will allow not only to protect the external environment, but to create jobs and reduce unemployment in the future. It is still important to support the state at all levels of implementation of programs for the economy digitalization. The results of the study can be used as a basis for formulating and adjusting strategies and programs for digitalization of the economies of different countries.
Verbivska L., Antokhov A., Zaremba O., Khishauyeva Z., & Issabayeva A. The development of e-commerce as a factor stimulating economic growth. Scientific Herald of Uzhhorod University. 2024. Р. 1165-1176.
Keywords: digitization; globalization; information technologies; digital platform; government programs.